(untitled) (Castilla. Estudios de Literatura, 2015)
It is beyond doubt that dances form part of the complex field of XVIth Century religious, secular and liturgical festivals. This paper considers dance as a manifestation of XVIth Century Corpus Christi and deals with a purely hermeneutical question: the way its role is ideologically legitimated into religious festivities, as well as some of its theatrical components. As a result of a process of integration of different codes in the complex of Early Renaissance theatre, we should think about dance from a typological point of view to understand its sense inside the performance